Development Of A Siaga DBD Application For Optimizing Epidemiological Investigation Of Dengue Fever In Malang City - Zuhriyah, Lilik (Journal of Innovation and Applied Technology, 2025)
Dengue fever cases in Malang City remain a concern,despite a downward trend in the last two years. As a Technical Implementation Unit, the  Community Health Center (puskesmas) have to carry out dengue cases Epidemiology Investigations (Penyelidikan epidemiologi/ PE), coordinated by the city health office . Reporting of dengue cases is often late. The Siaga DBD application is expected to help provide real-time and real-place dengue patient data. However, the application currently does not have a PE menu.To overcome reporting delays, it is necessary to add a menu for reporting dengue cases by puskesmas and hospitals as well as a PE menu in the SIAGA DBD application.